Identifikasi Kinerja Guru Dalam Menentukan Kualitas Mengajar Menggunakan Metode Profile Matching - Fitri Pranita Basution (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
To determine the quality of teacher performance, an educational institution must conduct a process of evaluating the performance of its teachers. MTsS YASPI College Foundation Labuhan Deli is one of the educational institutions that always improves the quality of education in schools. Teacher performance appraisal at Labuhan Deli YASPI schools is still done conventionally, so there are many assessment criteria and it takes a long time to evaluate the teacher's performance. This study aims to optimize the teacher performance appraisal process to be faster and more precise. The method used is Profile Matching. The results of this study can determine the teacher's performance more precisely by 100%. So that this research can be recommended as an appropriate system in evaluating teacher performance in schools